Agricultural Biotechnology: Opportunities and Challenges for the Philippines - William G. Padolina (Philippine Institute for Development Studies (PIDS), 2000)
Developing countries, still heavily dependent on agriculture, must now harness biotechnology to modernize agricultural production and diversify product outputs. The Philippines was one of the first Asian countries to establish a biotechnology research and development program. However, not much progress in harnessing the tools of biotechnology has been achieved, especially in the area of varietal improvement. Although there was an early realization of the importance of biotechnology in national agricultural development, there was little political will to provide resources for these programs to move forward. Modern biotechnology must be regarded as one of the tools in modernizing Philippine agriculture. Its role in varietal improvement, biosecurity, product standards, pest and disease prevention and management must be enhanced. A critical mass of highly trained human resources in the natural and social sciences that will undertake the research and development activities in agricultural biotechnology must be also be assured. Private sector participation in the development of agricultural biotechnology must be encouraged. The sustainability of these research and development activities can only in assured if they are able to serve commercial purposes. This may form the beginnings of an agricultural biotechnology industry and the much-needed commercial base for modern biotechnology to take-off in the country.
Keywords: 330; biotechnology; genetically modified organism; Artenvielfalt; Grüne Gentechnik; Philippinen